2012
DOI: 10.1089/cbr.2012.1200.271
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of VB6-845: An Anti-EpCAM Immunotoxin with Reduced Immunogenic Potential

Abstract: VB6-845 is a recombinant immunotoxin comprised of deBouganin (a de-immunized plant toxin) genetically linked to an epithelial cell adhesion molecule (EpCAM)-targeting humanized Fab fragment (4D5MOCB). EpCAM is highly expressed on a wide range of epithelial tumors but has limited expression on most normal epithelia and therefore represents an excellent target for immunotherapy. A comprehensive preclinical evaluation was performed to determine the safety and suitability of VB6-845 as a systemically administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Preclinical studies have suggested that this recombinant toxin is significantly less immunogenic than other payloads. Studies in mice demonstrated efficacy against EpCAM-positive solid tumors.VB6-845 caused severe vascular leak syndrome in rats at high doses but appeared to be better tolerated in cynomolgus monkeys [76]. A phase I study was opened in 2007 but closed for nonmedical reasons.…”
Section: Vb6-845mentioning
confidence: 99%
“…Preclinical studies have suggested that this recombinant toxin is significantly less immunogenic than other payloads. Studies in mice demonstrated efficacy against EpCAM-positive solid tumors.VB6-845 caused severe vascular leak syndrome in rats at high doses but appeared to be better tolerated in cynomolgus monkeys [76]. A phase I study was opened in 2007 but closed for nonmedical reasons.…”
Section: Vb6-845mentioning
confidence: 99%
“…Empowered by advances in experimental methodologies (Mazor et al, 2012; Cantor et al, 2011; Harding et al, 2010), epitope prediction tools (Wang et al, 2010; Bryson et al, 2010; Jawa et al, 2013), and protein design algorithms (Parker et al, 2013; Choi et al, 2013, King et al, 2014), T cell epitope deletion is being applied to a progressively larger number of therapeutic candidates. Early clinical data from epitope depleted biotherapeutics suggests that molecular engineering has had the desired effect in human patients (Morris et al, 2005; Entwistle et al, 2012), although to date there is no comparative clinical data for T cell epitope depleted and wild type versions of the same biotherapeutic. Deimmunized variants of Pseudomonas exotoxin should soon be entering clinical trials (Mazor et al, 2014), and comparison to results with the wild type immunotoxin SS1P (Kreitman et al, 2009) will provide new insights into the clinical utility of T cell epitope deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy studies in mice demonstrated that VB6-845 specifically and potently targeted EpCAM-positive tumors. High doses of VB6-845 administered to Cynomolgus monkeys were well-tolerated, and VB6-845 was proven to be minimally immunogenic in these monkeys [63]. …”
Section: Recombinant Immunotoxinsmentioning
confidence: 99%